PENDAMPINGAN KAJIAN KESELAMATAN LAYANAN DI UNIT RADIOLOGI RUMAH SAKIT PANTI WILASA DR. CIPTO SEMARANG - Muninggar, Jodelin; Rondonuwu, Ferdy S.; Sutresno, Adita; Maslebu, Giner; Wibowo, Nur Aji; Setiawan, Andreas; Putri, Dera Anastasya; Mayasari, Anisa (Universitas Kristen Satya Wacana Salatiga, 2023)
The Radiology Unit is a support unit to provide Radio Diagnostics and Radio Therapy service support. Patient safety studies that emphasize patient safety (Patient Savety) are the main thing and priority in every service provided. Panti Wilasa Dr Cipto Hospital as a Health Service Center in the Radiology Unit has conventional X-Ray, Fluoroscopy, Ultrasound, Panoramic, and CT Scan equipment, must also have Radiology Service Safety Standards. This standard is a reference in working on all types of services and equipment and levels for Radio Diagnostis and Radio Therapy. Until now, a Service Safety Study has not been prepared in the radiology unit. For this reason, it is necessary to assist the Service Safety Study in the Radiology Unit. The drafting team came from the Physics Study Program together with Level 7 Medical Physicists in the fields of Radio Diagnostics, Nuclear Medicine and Radiotherapy and Level 2 Medical Radiation Protection Officers.